A comparative analysis of competitive trade in a cluster market of the European Union: The Revealed Comparative Advantage (RCA) index - Edward O. Adigwe (Naše gospodarstvo / Our Economy, 2022)
This research is concerned with the comparative analysis of competitive trade within the cluster market economies of the European Union. The aim of this paper is to carry out trade analysis within the competing countries in the European market from 2009 to 2018 which represents the period after the global crisis of 2008 and prior to the Covid-19 pandemic of 2019 for the purpose of determining the extent of competitive trade within the European economies. The chosen metric is Béla Balassa's Revealed Comparative Advantage (RCA) index used for determining various countries' comparative advantage or disadvantage in trade. The findings show that the countries with RCA > 1 thrive economically in comparison to other competing lower economies. And the fact that the European Union economy thrives on mechanized trade other than agricultural products irrespective of the competitive market. This study is a significant contribution towards improving the Ricardian model of comparative advantage on trade within a cluster market in the European economies.
Keywords: P51; C82; F14; 330; competitiveness; revealed comparative advantage; international trade